Intellectual property rights: legal and economic challenges for development - Cimoli, Mario (The initiative for policy dialogue series, 2014)
In recent years, intellectual property rights both in the form of patents and copyrights have expanded in their coverage, the width and depth of protection, and the tightness in their enforcement. Moreover, for the first time in history, the IPR regime has become increasingly uniform at international level by means of the TRIPS agreement, irrespectively of the degrees of development of the various countries. The book addresses the effects of IPR on the processes of innovation and innovation diffusion, and provides detailed discussions of possible policy measures within the current TRIPS regime.